The Effect of Occupational Therapy on Increasing Functional Independence in Patients with Mental Disorders - Lianur, Lianur; Haryani, Amaliyah; Putri, Mega Ilfa (Trigin Institute, 2025)
This research explores the effect of occupational therapy (OT) on patients with mental disorders, focusing on its role in increasing functional independence and improving daily living skills. Mental disorders often lead to impairments in self-care, social interactions, work capabilities, and other essential life activities, reducing overall independence. This study examines how OT interventions, tailored to individual needs, can address these challenges and enhance patients' autonomy and quality of life. The research synthesizes prior literature on OT's impact in mental health settings and presents a comprehensive evaluation of its effectiveness in fostering independence. Results suggest that OT significantly improves self-care skills, social participation, and vocational engagement, contributing to better mental health outcomes. The findings underscore the importance of integrating occupational therapy into clinical practice and healthcare policy, advocating for broader accessibility to OT services as part of a holistic approach to mental health treatment. This study concludes that occupational therapy is a valuable intervention for patients with mental disorders, promoting long-term recovery and enhancing functional independence in daily life.